Biobased lubricants and greases : technology and products - Honary, Lou A. T.; Richter, Erwin William, 1934- (Hoboken, N.J. : Wiley, 2011)
Due to the rise in petroleum prices as well as increasing environmental concerns, there is a need to develop biochemicals and bioproducts that offer realistic alternatives to their traditional counterparts; this book will address the lack of a centralized resource of information on lubricants and greases from renewable sources, and will be useful to a wide audience in industry and academia. It is based on 20 years of research and development at the UNI-NABL Center, and discusses the various types of vegetable oils available, comparing their characteristics, properties and benefits against thos.
Front Matter -- Colour Plates -- Historical Development of Vegetable Oil-Based Lubricants -- Chemistry of Lubricants -- Petroleum-Based Lubricants -- Plant Oils -- Synthetic Based Lubricants: Petroleum-Derived and Vegetable Oil-Derived -- Genetic Modification and Industrial Crops -- Biobased Lubricants Technology -- Performance Properties of Industrial Lubricants -- Biobased and Petroleum-Based Greases -- Factors Affecting the Environment -- List of Useful Organizations -- Useful Test Methods -- Glossary -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Vegetable oils as fuel; Lubricating oils -- Biocompatibility; Plant biotechnology; Biomass energy; Lubricating oils -- Biocompatibility; Engineering; Chemical engineering; TECHNOLOGY & ENGINEERING -- Petroleum; Electronic books; Electronic books